Pengaruh Struktur Modal, Total Asset Turn Over, Dan Current Ratio Terhadap Kinerja Keuangan Pada PT Kalbe Farma Tbk Periode 2015-2024 - Muhammad Aulia Tanshir Saragih; Koes Indrakoesoema (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of Debt to equity Ratio, Total Asset Turnover, and Current Ratio on Return on Assets, both partially and simultaneously, at PT Kalbe Farma Tbk during the period 2015-2024. This study uses a descriptive method with a quantitative Approach. So the analysis is focused on the processing and interpretation of numerical data sourced from the company's annual financial statements. The data used are secondary data obtained from the financial position statement and income statement, which are published consistently during the observation period and are considered representative in describing the company's financial condition over time. Data analysis is carried out through several stages, starting from classical assumption testing to multiple linear regression analysis. To assess the feasibility of the research model, correlation coefficient tests, determination coefficients, simultaneous tests (F), and partial tests (t) are used with the help of EViews 12 software. The test results show that DER has no significant effect on ROA, with a significance value of 0.1715 which is greater than the significance level of 0.05. Similar results were found for CR, which had a significance value of 0.3738, thus not being proven to have an effect on ROA. In contrast to TATO, this variable actually showed a positive and significant effect on ROA with a significance value of 0.0354, indicating that asset utilization efficiency plays a significant role in increasing company profitability. Meanwhile, the results of the simultaneous test showed that DER, TATO, and CR together did not have a significant effect on ROA, with a probability value of 0.068577. However, the Adjusted R² value of 0.503867 indicates that the research model is able to explain 50.39% of the variation in ROA. Meanwhile, the remaining 49.61% is influenced by other factors outside the analyzed variables.